The use of training in graduate recruitment: Emerging trends and business opportunities - Kennard, Michael James (2007)
The initial aim of the management project was to review the UK training industry, identify and investigate a suitable research topic, and use this work to identify a business opportunity and develop a business plan. Following a literature review the research has focused on investigating how employers utilise training programmes to attract graduate recruits compared with four other factors: financial benefits; corporate identity; quality of life; and the nature of the work itself. The methodology employed was semi-quantitative content analysis on the graduate recruitment websites of 15 FTSE 100 companies across 5 business sectors:-